Postoperative Outcomes of Modified Carnoy’s Solution versus 5-Fluorouracil for Chemical Cauterisation following Enucleation and Peripheral Ostectomy in Patients with Odontogenic Keratocyst: A Research Protocol - Nidhi Vijay Kumar Bodiwala; Nitin Bhola (Journal of Clinical and Diagnostic Research)
Introduction: An Odontogenic Keratocyst (OKC) is always a topic of debate due to its distinct biological behaviour to recur after surgical procedure. Also, it has an odyssey cyst-tumour-cyst from 1956 to 2005 to 2017. For this reason, number of treatment modalities was cited in the literature. Modified Carnoy’s Solution (MCS) is commonly used due to its effectiveness, while 5FU, an antimetabolite used in cancer treatment, presents a newer approach. Need of the study: The varying Recurrence Rate (RR) and postoperative complications associated with different treatment modalities for OKC. While MCS is a commonly used adjuvant therapy due to its effectiveness, and bone resection minimises recurrence but leads to severe functional and aesthetic issues, there is limited data comparing the efficacy of MCS to newer agents like 5-Fluorouracil (5FU) in reducing recurrence. Evaluating the effectiveness of 5FU, a promising chemotherapeutic agent, could potentially offer a less invasive and equally effective treatment option for reducing recurrence and improving patient outcomes in OKC management. Aim: To compare and evaluate the postoperative outcomes, specifically the RR, of MCS vs 5FU used for chemical cauterisation following enucleation and peripheral ostectomy in patients with OKC. Materials and Methods: An experimental in-vivo study will be conducted in the Department of Oral and Maxillofacial Surgery, Sharad Pawar Dental College, Datta Meghe Institute of Higher Education and Research (DMIHER), Sawangi (M), Wardha, Maharashtra, India, from April 2023 to March 2024. The approach involves categorising 12 histologically proven cases of OKC into two groups according to distinct adjunct techniques used (six patients in each group). Group A includes subjects treated with MCS. Group B includes subjects with 5FU. Postoperative outcomes will be evaluated and compared among the groups. The data will be analysed and compared using Student's t-test and Mann-Whitney U test. It will be used at a 5% level of significance (p-value ≤0.05).